Antibiotic stewardship: what for? - Amábile-Cuevas, Carlos F. (Frontiers in Antibiotics, 2025)
Antibiotic stewardship programs and controlled antibiotic usage have long been considered fundamental strategies in healthcare systems, and these approaches were traditionally viewed as the primary defense against bacterial resistance development. But recent studies reveal a surprising disconnect between antibiotic usage and resistance patterns, with socioeconomic factors showing stronger correlations than clinical drug use. Multiple factors beyond antibiotic consumption now influence resistance patterns, including agricultural antibiotic use, increasing urbanization, and the evolution of mobile genetic elements. Therefore, while antibiotic stewardship remains crucial for preventing side effects and reducing healthcare costs, its role in controlling bacterial resistance requires fundamental reassessment. This understanding necessitates a strategic shift in stewardship programs to focus on more attainable goals, such as patient safety and cost reduction, while developing new, comprehensive approaches to address antibiotic resistance that account for the complex interplay of biological, environmental, and socioeconomic factors.